High-level Dialogue Meeting on Gender and Climate change in South Asia - Kumar, Aruna T. (CGIAR System Organization, 2023)
Like many other regions across the globe, South Asia is grappling with the challenges posed by climate change. World Bank estimates that 750 million people in South Asia have been affected by at least one climate-related disaster. The hazards and extreme weather events range from cyclones, monsoon rainfall variability, floods, heat waves, increased average temperatures and salinity in coastal areas, jeopardizing food security and people’s livelihoods. Amid these challenges, South Asian countries are working towards increasing women’s and girls’ rights, disrupting access to empowerment opportunities and essential resources. The CGIAR Gender Equality Research Initiative, HER+, aims to counter the challenges of growing inequalities due to climate change and bolster climate resilience by dismantling structural barriers to gender equality in agrifood systems. In 2022, HER+ organized the first high-level dialogue on gender and climate change in Nairobi, followed by a second dialogue in New Delhi on October 13, 2023. The latter facilitated knowledge exchange on challenges and solutions for gender equality and climate resilience in agrifood systems across India and the wider South Asia region. It welcomed stakeholders from various sectors— government officials, farmer representatives, gender and climate experts, researchers, the private sector, and donors.